The picosecond laser for tattoo removal. Issue 8 (November 2016) - Hsu, Vincent; Aldahan, Adam; Mlacker, Stephanie; Shah, Vidhi; Nouri, Keyvan
Abstract The prevalence of tattoos continues to grow as modern society's stigma towards this form of body art shifts towards greater acceptance. Approximately one third of Americans aged 18–25 and 40 % of Americans aged 26–40 are tattooed. As tattoos continue to rise in popularity, so has the demand for an effective method of tattoo removal such as lasers. The various colors of tattoo inks render them ideal targets for specific lasers using the principle of selective photothermolysis. Traditional laser modalities employed for tattoo removal operate on pulse durations in the nanosecond domain. However, this pulse duration range is still too long to effectively break ink into small enough particles. Picosecond (10−12 ) lasers have emerged at the forefront of laser tattoo removal due to their shorter pulse lengths, leading to quicker heating of the target chromophores, and consequently, more effective tattoo clearance. Recent studies have cited more effective treatment outcomes using picosecond lasers. Future comparative studies between picosecond lasers of various settings are necessary to determine optimal laser parameters for tattoo clearance.